Pengaruh Korosi terhadap Kekuatan Tarik Macaroni Tubing P110 1.900" x 4.19 lbs/ft - Heribertus Sukarjo; Adi Surahman (Jurnal Engine: Energi, Manufaktur, dan Material, 2017)
Macaroni Tubing P110 1.900″ x 4.19 lbs/ft which applicated at Snubbing and Oil and Gas industry, exposed to Corrosive fluids such as NH4Cl, KCl and Sea Water. Macaroni Tubing P110 1.900″ x 4.19 lbs/ft also has mechanical treatment especially Tensile force. That’s why effects of NH4Cl, KCl and Sea Water fluid to Corrosion Rate and Tensile strength Macaroni Tubing P110 1.900″ x 4.19 lbs/ft shall be known. Starting from those issue, Immersion corrosion testing using NH4Cl, KCL and sea wáter instruments is conducted, and Tension testing is performed to the material after exposed to those corrosive fluids. Immersion corrosion testing method is used to analyze corrosion rate and Tension testing is used to analyze the tensile strength. The result shown that the fastest Corrosion rate is material which immersed to 6% NH4Cl with average corrosion rate value 0,210 mm/year. In second position is material which immersed to 3% KCl with average corrosion rate value 0.132 mm/year and the latest is material which immersed to sea water with average corrosion rate value 0.095 mm/year. Meanwhile, tensile strength test shown 676.53 Mpa for Raw Material specimens, 664.19 Mpa for specimens which immersed to 3% KCl, 653.51 Mpa for specimens which immersed to 6% NH4Cl and 669.55 Mpa for specimens which immersed to sea water. From those three specimens which immersed to corrosive fluid shown tensile strength decreased than Raw Material tensile strength and Specimen which immersed to 6% NH4Cl shown the biggest value.